2020
DOI: 10.1684/epd.2020.1155
|View full text |Cite
|
Sign up to set email alerts
|

HMGB‐1, TLR4, IL‐1R1, TNF‐α, and IL‐1β: novel epilepsy markers?

Abstract: Aim: The purpose of this study was to compare HMGB‐1, TLR4, IL‐1β, IL‐1R1, and TNF‐α levels in patients with mild and severe epilepsy with those in a healthy control group. Methods: Children aged 4–17 years, diagnosed with epilepsy for at least three years and with no progressive neurological disease, metabolic disease or infection, were selected for the study. The severe epilepsy group consisted of 28 children with at least one episode a week despite receiving three or more antiepileptic drugs. The mild epile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 55 publications
(80 reference statements)
1
29
0
Order By: Relevance
“…Inflammatory mediators may also have diagnostic potential since levels of several inflammatory molecules have been found to be altered in the blood of patients with epilepsy [ 11 ]. This includes cytokines such as the pro-inflammatory cytokine IL-1β [ 12 , 13 , 14 , 15 ], HMGB1 [ 16 ], and the inflammation marker C-Reactive protein (CRP) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory mediators may also have diagnostic potential since levels of several inflammatory molecules have been found to be altered in the blood of patients with epilepsy [ 11 ]. This includes cytokines such as the pro-inflammatory cytokine IL-1β [ 12 , 13 , 14 , 15 ], HMGB1 [ 16 ], and the inflammation marker C-Reactive protein (CRP) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown P2X7R protein levels to be increased in the plasma of patients with underlying inflammation [ 30 ], including patients following sepsis [ 31 ]. Moreover, the expression of several cytokines downstream of P2X7R activation (e.g., IL-1β, IL-18) has been found altered in the blood of patients with epilepsy [ 12 , 13 , 14 , 15 , 32 ]. Whether P2X7R-dependent signaling can be used to support the diagnosis of epilepsy, has, however, not been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…Low-dose TNFα (5.0 μg/kg) significantly increased the frequency of epilepsy and prolonged the duration of neuronal firing [39,40]. The content of TNF-α was positively correlated with the severity of epilepsy, which was higher in the severe epilepsy group than in the mild group, while the nonepileptic group is at a minimum level [41]. Tumor necrosis factor is mainly involved in the pathological process of seizures through two receptors, which will induce seizures by binding receptor 1, while the activation of receptor 2 will exert anticonvulsant effects.…”
Section: Tumor Necrosismentioning
confidence: 96%
“…The complex interactions between immune‐inflammatory processes, cytokine activation, and genetic factors play important roles in the development of FS 99,100 . The levels of blood HMGB1 and IL‐1β in children with FS after 30 min of seizure attacks were significantly higher than those with fever only, and these two inflammatory indicators were correlated with each other 101–103 . HMGB1 contributes to the onset of FS and plays an important role in the occurrence of secondary epilepsy associated with the prolongation of FS, 104 and the occurrence of adult epilepsy is related to the recurrence of FS in childhood 105 .…”
Section: Role Of Hmgb1 In Pediatric Diseasesmentioning
confidence: 98%
“…HMGB1 contributes to the onset of FS and plays an important role in the occurrence of secondary epilepsy associated with the prolongation of FS, 104 and the occurrence of adult epilepsy is related to the recurrence of FS in childhood 105 . Similar to that of FS, serum HMGB1 was significantly elevated within 24 h of seizures in children with epilepsy and had the potential to predict seizure frequency and prognosis more accurately than IL‐1β 103,106 . Data from different experimental models of acute and chronic epilepsy have shown that HMGB1‐TLR4 signaling in the hippocampus plays a key role in the generation and recurrence of seizures 107 .…”
Section: Role Of Hmgb1 In Pediatric Diseasesmentioning
confidence: 99%